Taking Stock of Antidumping, Safeguards, and Countervailing Duties, 1990-2009 - Bown, Chad P. (World Bank, Washington, DC, 2014)
This paper examines the evolving, cross-country use of antidumping, safeguard, and countervailing duty policies -- temporary trade barriers (TTBs) -- over the period 1990-2009. The author constructs two new measures of imported products subject to the combined use of these TTBs before applying these measures to new data drawn from the World Bank's Temporary Trade Barriers Database. The research establishes a number of facts regarding trends in historical use to benchmark against policy activity during the global economic crisis of 2008-2009. The 2008-2009 economic shock mostly accentuates patterns and trends already visible in the pre-crisis data: e.g., while the major users of such policies overall combined to increase the product lines subject to TTBs by 25 percent during the crisis, this was driven almost entirely by developing economies which increased their product coverage by 40 percent. On the export side, a previously unidentified feature of the data is that a much larger share of China's exports to other developing economies is subject to foreign-imposed antidumping than its exports to developed economies. The evidence confirms this feature is shared by a number of other major developing economy exporters, deepening concern that these discriminatory trade barriers are increasingly a "South-South" phenomenon.